Geophysical Evaluation of Cemetries for Groundwater Contamination in Dutsin-Ma, Katsina State - Ahmad, Ubaidullah; Hamza, Abubakar Abdullahi; Abdulwahab, Usman; Atiku, Anwaru; Yusuf, Tajuddeen Batsari; Aminu, Idris Usman (FUDMA Journal of Sciences, 2026)
The increasing reliance on shallow groundwater sources in Dutsinma, Katsina State, has raised concerns about contamination risks from nearby cemeteries. This study applied 2D Electrical Resistivity Imaging (ERI) to investigate groundwater contamination around Dutsinma cemeteries. A total of six survey profiles were established using the dipole dipole electrode configuration with 5 m interelectrode spacing covering a total spread length of 200 m. ABEM SAS4000 terrameter was used for this survey, and inversion was performed using RES2DINV software to produce 2D resistivity models of the subsurface. All 2D resistivity models showed resistivity varying from 9.99 Ωm to 4226.0 Ωm to a maximum depth of about 21.5 m, interpreted as leachate plumes originating from the decomposition of buried remains. Regions with resistivity values < 20 Ωm suggest regions contaminated with leachate. These conductive anomalies extended beyond some of the cemetery boundary indicating lateral migration of contaminants controlled by the permeable weathered basement underlying the area. The findings demonstrates that 2D ERI is an effective, non-invasive geophysical tool for mapping cemetery-related leachate migration and assessing potential threats to shallow aquifers. The result revealed that the subsurface is composed of distinct lithological layers with the low resistivity values observed suggesting the presence of possibly contaminated materials influenced by decomposed remains and also provides valuable insights into the extent and possible pathways of contamination within the study area, which can support sustainable groundwater management and burial ground sighting in the study area.
Keywords: Groundwater Contamination; Leachate; Resistivity; Cemetery